The contribution of a person-centred model of Lean Six Sigma to the development of a healthful culture of health systems improvement - Teeling, Seán Paul; Baldie, Deborah; Daly, Ailish; Keown, Anne Marie; Igoe, Aileen; Dowling, Ciara; McNamara, Martin (Frontiers in Health Services, 2025)
BackgroundA failure to distinguish between person-centredness, person-centred care, and person-centred cultures can result in improvement initiatives focusing solely on improvement initiative metrics and outcomes, excluding the authentic experiences of patients and staff. Building on the foundational work of Dewing and McCormack, we have designed, piloted, and implemented the Person-centred Lean Six Sigma (PCLSS) model in public and private acute and community healthcare settings across Ireland. This model uses Lean Six Sigma, a widely adopted improvement methodology, through a person-centred lens with which improvement practitioners and healthcare staff can inspect their Lean Six Sigma practice and critically evaluate whether, to what extent, and how it is synergistic with person-centred approaches.AimThis paper explores the deployment of the PCLSS model across four clinical study sites and examines its alignment with McCance and McCormack's conceptual work on healthful cultures, evaluating its contribution to creating cultures that support sustainable improvement, compassion, and respect.MethodsThe PCLSS model was embedded within a university-accredited education programme for healthcare staff. The model was applied across four distinct healthcare settings in Ireland: a public acute teaching hospital, a private full-service acute hospital, an integrated ophthalmology service bridging hospital and community care, and a public rehabilitation hospital. A case study methodology was used to examine implementation and impact.ResultsAcross all four sites, the PCLSS model facilitated improvements in operational efficiency, staff and patient engagement, interprofessional collaboration, and reflective practice. The model supported leadership at all levels, fostered sustainable change, and successfully mapped onto key domains associated with healthful cultures, as articulated in the work of McCance and McCormack.ConclusionThe PCLSS model represents a sustainable, values-based approach to improvement that aligns operational excellence with person-centred principles. Its application contributes meaningfully to the development of healthful cultures in healthcare organisations.